Faktor-faktor yang Mempengaruhi Biaya Produksi, Biaya Operasional, Penjualan, Modal Kerja, dan Perputaran Total Aset - Nikhlatul Hasanah; Fitri Nuraini; Gita Desipradani (UMSurabaya Publishing, 2026)
Non-essential consumer goods companies are those whose products are highly sensitive to changes in the economic cycle. Fluctuations in purchasing power after the pandemic require companies to optimize cost and asset efficiency in order to maintain profit performance. This study aims to analyze the effect of production costs, operating costs, sales, working capital, and total asset turnover on net profit in non-primary consumer goods manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The research method used is quantitative. The study sample comprises 10 companies in the non-primary consumer goods sector selected using purposive sampling. The research utilizes secondary data derived from corporate financial statements. Data analysis is conducted through descriptive statistics, classical assumption testing, multiple linear regression analysis, and hypothesis testing using SPSS version 25. The partial test results (t-test) indicate that production costs, operating costs, sales, working capital, and total asset turnover each have a significant impact on net profit. Additionally, the simultaneous test results (F-test) demonstrate that these variables collectively exert a significant influence on net profit.